Novels - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2021)
The study of society today is divided into different disciplines – the so-called social sciences – a division that fractures our consciousness into disconnected bits and pieces. Literature does the very opposite: it brings things together, offering glimpses into the enfolded, hologramic nature of society. Here are some of the novels that helped us understand this hologramic enfoldment from different angles. They are all worth reading.
Keywords: P16; 330; literature; political economy